Partially Reduced Ni-NiO-TiO2 Photocatalysts for Hydrogen Production from Methanol-Water Solution - Drobná, Helena; Meinhardová, Vendula; Dubnová, Lada; Kozumplíková, Kateřina; Reli, Martin; Koci, Kamila; Čapek, Libor (MDPI, 2023)
The study compares the photocatalytic behavior of TiO2, NiO-TiO2, and Ni-NiO-TiO2 photocatalysts in photocatalytic hydrogen production from methanol-water solution. TiO2 and NiO-TiO2 photocatalysts with theoretical NiO loading of 0.5, 1.0, and 3.0 wt. % of NiO were prepared by the sol-gel method. The Ni-NiO-TiO2 photocatalysts were prepared by partial reduction of NiO-TiO2 in hydrogen at 450 degrees C. The Ni-NiO-TiO2 photocatalysts showed significantly higher hydrogen production than the NiO-TiO2 photocatalysts. The structural, textural, redox, and optical properties of all of the prepared photocatalysts were studied by using XRD, SEM, N-2- adsorption, XPS, H-2-TPR, and DRS. Attention is focused on the contribution of Ni loading, the surface composition (Ni2+, the lattice O2- species, and OH groups), the distribution of Ni species (dispersed NiO species, crystalline NiO phase, and the metallic Ni-0 species), oxygen vacancies, TiO2 modification, the TiO2 crystallite size, and the specific surface area.
Částečně redukované Ni-NiO-TiO2 fotokatalyzátory pro produkci vodíku z vodného roztoku metanolu
Keywords: Ni-NiO-TiO2; water splitting; Ni-NiO co-effect; Ni-NiO-TiO2; produkce vodíku; Ni-NiO efekt